The interrelationship between sleep disturbance symptoms and aggression before and after the campus closure of the COVID-19 pandemic: insight from a cross-lagged panel network model - Jinhua Zou; Baohua Bian; Min Li; Gang Liu (Frontiers Media S.A., 2024)
BackgroundThe COVID-19 pandemic is detrimental to sleep quality and increases aggression among college students. Nevertheless, relevant studies were rare. Hence, we collected longitudinal data during and post-campus closure in the current study to investigate the relationship between sleep disturbance and aggression.MethodsData from 665 college students (59.2% females, Meanage = 19.01, SD age = 1.25) were collected before (wave 1) and after (wave 2) the campus closure of COVID-19. All participants were asked to fill out the Buss-Perry Aggression Questionnaire and the Youth Self-Rating Insomnia Scale. Two symptom networks and a cross-lagged panel network were formed and tested.ResultsHostility has the highest centrality in the symptom network both in waves 1 and 2, and it bridges sleep disturbance and aggression. "Easily be woken" - "wake up too early" and "wake up with tired" - "function hindrance" are two important symptom associations in networks of waves 1 and 2. All symptoms except "difficulty in falling asleep" and "easily be woken" ameliorated after closure. Moreover, "physical aggression" and "hostility" can trigger other symptoms in wave 2.ConclusionAs the first study about aggression and sleep disturbance in the background of COVID-19, we provide valuable information about the relationship between sleep disturbance and aggression on the symptom dimension.